Disruption in an alluvial landscape: Settlement and environment dynamics on the alluvium of the river Dyje at the Pohansko archaeological site (Czech Republic). (30th March 2019) - Petřík, Jan; Petr, Libor; Adameková, Katarína; Prišťáková, Michaela; Potůčková, Anna; Lenďáková, Zuzana; Frączek, Marcin; Dresler, Petr; Macháček, Jiří; Kalicki, Tomasz; Lisá, Lenka
Abstract: Floodplain alluvia can provide a combination of natural and anthropogenic evidence of environmental changes, allowing to directly examine their evolution in relation to settlement dynamics. Such evidence is recorded, for example, at the archaeological site Pohansko by the town of Břeclav, a former centre of the Great Moravian Empire. The aim of our research was to explore what conditions on the floodplain could have caused the abandonment of this environment. Special attention was paid to the climax of the floodplain's occupation during the times of the Great Moravian Empire (AD 836–906) and to the decline of its occupation in the following centuries. The environmental record at the Pohansko site starts in the 7th century BC. From the Iron Age onwards (Hallstatt and La Tène periods) there is evidence of non-agricultural human activities. Since the 3rd and 2nd centuries BC to at least the second half of the 10th century AD, there is no record of any floodplain aggradation or flooding at the site. Later, both the archaeological and palaeoecological records on the floodplain probably got exposed and redeposited. The result is a mechanically disturbed layer that is synchronous with soil horizons and subsequent Early Mediaeval cultural layers covering sandy elevations. For an unknown reason, the site was deserted for many centuries after the end of the 10th century AD. During the High Mediaeval period and the early Modern Era, especially since the 15th century AD, overbank deposits covered the floodplain. Intensified human impact in the river catchment and climate change during the Little Ice Age were the main triggers of this change. The results correlate with the written historical sources pertaining to this area, which speak about an increasing frequency of flooding in the Czech lands since the 14th century, and especially in the second half of the 16th century. As a result, these sites became unsuitable for settlement and abandoned.